Experimental research for biomass steam gasification in a fluidized bed. Issue 16 (18th August 2019) - Yang, H.M.; Liu, J.G.; Zhang, H.; Han, X.X.; Jiang, X.M.
ABSTRACT: A fluidized bed gasification system was built to investigate the biomass steam gasification performance in different conditions. Medium heating value syngas with 34% H2 content and no more than 20 g/Nm 3 tar content could be obtained under 800°C with a S/B (steam vs. biomass ratio) of 0.9 by using olivine as bed material. The results indicated that syngas quality (including H2 content, gasification efficiency, tar reduction, etc.) is in a positive correlation with temperature and S/B, but has a negative correlation with fluidization number (FN). Compared with quartz sand and dolomite, olivine is more suitable for fluidized bed because of its catalytic ability and good abrasion performance for fluidized bed gasifier. As a result, a set of optimum parameters is recommended with S/B of 0.9~1.0, FN of 1.4, and temperature of 800°C in this study. Tar is a by-product from the gasification process, which will cause the pipeline congestion, reduce the gasification efficiency, and deteriorate the working condition. According to this experiment, the temperature and S/B both have a negative effect on tar content, while tar content increased with increase in the FN. Dolomite and olivine both have an inhibition function on tar, and the olivine is considered the best choice of bed material because of its good anti-wear properties.